Studi Pengetahuan Masyarakat Mengenai Gulma Air Sebagai Bioindikator Pencemaran Air Di Desa Lambur Luar Kabupaten Tanjung Jabung Timur - NINING NURAIDA; TRY SUSANTI (INSTITUT AGAMA ISLAM NEGERI AMBON, 2019)
The number of aquatic plants along the river flow outside the village of Lambur becomes a barrier to water traffic so that these plants are classified to be weeds or a nuisance for local people. This study aims to determine and document the types of weeds found in the village of Lambur and explore locals’ knowledge about the types of existing water weeds and their use. This research was conducted in the Village of Lambur Luar Tanjung Jabung Timur District by using the roaming method to collect existing Weed samples. Data collection is done by observation, interviews, documentation and literature studies, the data are analysed descriptive qualitative design. The results showed that there were 19 species and 13 families of water weeds, namely: Fimbristylis sp1, fimbristylis sp2, Cyperus sphacelatus Rottb, Blyxa aubertii Rich, Lindernia sp, Glinus oppositifolius (L.) Aug.DC, Melastoma malabathticum L, Nymphaea nouchali Burn, Ludwigia hyssopifolia (G.Don) Exell, Ludwigia repens JR Forst, Scoparia dulcis, Hippochaete debilis (Roxb.ex Vaucher) Ching, Panicum repens L, Oryza sativa, Persicaria hydropiper L, Monochoria vaginalis (Burm.f.) C.Presl, Borreria alata (Aubl.) DC, Borreria repens DC, and Xyris sp. Of the 19 species found, only 12 species, the locals know the name of the water weed, 7 species are only referred to as grass only by the locals, this water weed is not used by the them but mostly weeds are used for animal feed, the researchers provide education to the community that actually weed water can be used for treatment and to find out the quality of a waters or be used as an indicator of the biological condition of a river in wheteher good condition or not. Keywords: Knowledge Studies, Lambur Luar, Water Weeds